Dulaan a documentary on the Philippine theater - Cultural Center of the Philippines; Tiongson, Nicanor (Manila CCP, 1989)
Features the varied and colorful traditions that shaped theater in the Philippines. These include indigenous rituals and dances; the Spanish-influenced komedya, sinakulo, sarsuela and drama; the American-influenced bodabil and modern "legitimate" plays; and the realistic and expressionistic plays of today.
VHS.
Narration, Dindo Angeles.
Keywords: Theater -- History. -- Philippines; Theater art; Humanities; Philippine literature